briandaleux
18

# Resoudre les équations suivantes: a) (2x-3)(5x+1)+(2x-3)(3x-4) = 0 b) (5x-2)(5x-10)-(3x+2)(5x-10) = 0 c) (3x-1)(x-3)-(x-3)² = 0

(2) Réponses
marieonette

(2x - 3)(5x + 1) + (2x - 3)(3x - 4) = 0 (2x - 3)(5x + 1 + 3x - 4) = 0 (2x - 3)(8x - 3) = 0 (5x - 2)(5x - 10) - (3x + 2)(5x - 10) = 0 (5x - 10)(5x - 2 - 3x - 2) = 0 (5x - 10)(2x - 4) = 0 (3x - 1)(x - 3) - (x - 3)² = 0 (x - 3)(3x - 1 - x + 3) = 0 (x - 3)(2x + 2) = 0 J'ai factorisé, maintenant tu n'as plus qu'à résoudre!

galeleeseuwo

a) (2x-3)(5x+1)+(2x-3)(3x-4) = 0 (2x-3)(5x+1+3x-4) =0(2x-3)(8x-3) =02x-3 =0                          8x-3 =0x =3/2                              x = 3/8 b) (5x-2)(5x-10)-(3x+2)(5x-10) = 0(5x-10)(5x-2-3x-2) =0(5x-10)(2x-4) =05x-10 =0                          2x-4 =0x = 10/5                             x =4/2x = 2                                  x = 2solution (2)  c) (3x-1)(x-3)-(x-3)² = 0 (x-3)(3x-1-x+3) =0(x-3)(2x+2) =0x-3 =0          2x+2 =0x = 3            x =2/2 =1

Ajouter une réponse